Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1111/j.1600-0714.1990.tb00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of oral mucosal lesions, the influence of tobacco habits and an estimate of treatment time in an adult Swedish population

Abstract: A randomly selected sample of adult subjects living in a Swedish county was examined for the presence of oral mucosal lesions. Nine hundred twenty (920, 95%) of the selected sample of 967 subjects, comprising approximately 0.75% of the total adult population, were examined; lesions were registered in 596 of the 920. The registered prevalence levels were very similar to earlier reported data from Sweden. Further, the relationship between tobacco habits and mucosal lesions was analyzed and the time needed for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
85
14
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 8 publications
21
85
14
3
Order By: Relevance
“…As reported by other authors, denture-related stomatitis, hyperplasia and traumatic ulcer were the most common problems among denture wearers [8,32,42] . Salonen et al [43] and KovacKovacic and Skaleric [14] reported that DRL are most common among women; the present investigators found no sex-related differences for denture-associated conditions [14,43] . The positive influence of denture age on the presence of oral mucosal lesions has been reported before [40,44,45] .…”
Section: Discussionmentioning
confidence: 34%
See 1 more Smart Citation
“…As reported by other authors, denture-related stomatitis, hyperplasia and traumatic ulcer were the most common problems among denture wearers [8,32,42] . Salonen et al [43] and KovacKovacic and Skaleric [14] reported that DRL are most common among women; the present investigators found no sex-related differences for denture-associated conditions [14,43] . The positive influence of denture age on the presence of oral mucosal lesions has been reported before [40,44,45] .…”
Section: Discussionmentioning
confidence: 34%
“…25.1% of the individuals had poor oral hygiene in our study sample, while the oral hygiene status of 24% subjects was defined as moderate. The presence of denture hyperplasia was higher in individuals with poor oral hygiene in the present study [2,[42][43][44][45]53] . This supports the need for continuing efforts to develop more efficient oral hygiene methods for the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…5). It is closely related to smoking habits [100,101], and the prevalence is 1-2% in Scandinavia. Smoker's palate is not premalignant [102], whereas the palatal keratosis associated with reverse smoking, as seen primarily in Asia, is a premalignant lesion [103].…”
Section: Smoker's Palatementioning
confidence: 99%
“…The changes are symptomless, it is not premalignant, and it seems that the pigmentation is reversible upon smoking cessation [104,106]. Hairy tongue and coated tongue are other harmless lesions related to smoking, although they can be seen in nonsmokers as well [100,101,107].…”
Section: Smoker's Melanosis and Hairy Tonguementioning
confidence: 99%
“…Sa prévalence est de 1 à 2 % dans la population générale [1] . L'intérêt de cette pathologie est due à la difficulté de son traitement ainsi qu'à son éventuelle transformation maligne, essentiellement pour les formes érosives et chroniques.…”
unclassified